SCIENTIFIC PRINCIPLES OF PEDAGOGICAL MODELING FOR THE DEVELOPMENT OF DIAGNOSTIC COMPETENCE OF FOREIGN LANGUAGE TEACHERS AT HIGHER MILITARY EDUCATIONAL INSTITUTIONS WITHIN THE SYSTEM OF POSTGRADUATE EDUCATION - Hryshchuk, Yuliia (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article analyzes the scientific foundations of pedagogical modeling of the development of diagnostic competence of foreign language teachers of higher military educational institutions within the framework of postgraduate education. It emphasizes that pedagogical modeling is the subject of research for a wide range of Ukrainian and foreign scholars who provide various interpretations of the concept of “pedagogical modeling”. The purpose of the article is to analyze the theoretical and practical foundations of modern pedagogical science regarding the issue of pedagogical modeling of the development of diagnostic competence of foreign language teachers of higher military educational institutions within the system of postgraduate education and to characterize its main stages. Research methods: analysis, synthesis, comparison, systematization of scientific and pedagogical sources dedicated to the study of pedagogical modeling of the formation and development of professional competencies. Results: based on the analysis of scientific studies on the discussed issue, the main stages of pedagogical modeling of the development of diagnostic competence of foreign language teachers of higher military educational institutions were investigated and characterized. These stages include goal setting (analysis of needs and professional context), planning (preparation for program development, creation, or improvement and provision of necessary resources), model design (formulation of specific tasks), methodic development (creation of clear activity algorithms and selection of methods, techniques, tools), determination of criteria for assessing the development of diagnostic competence of foreign language teachers of higher military educational institutions (uniting all aspects of its manifestation, serving to clarify the effectiveness of the model’s functioning), and implementation (integration of defined approaches, principles, methodic, diagnostic tools). The article outlines the prospects for further research on the discussed issue